Improving Service Quality Of Delivery Services Based On Heterogeneous Customer Behavior In A Developing Country: A Context During Covid-19 - Muslimin, Rahmat Hidayat; Darmawan, Armin; Bahri, Syamsul; Rapi, Amrin (Jurnal Manajemen Industri dan Logistik, 2022)
Delivery services are going through a transition phase globally due to changes in the market dynamics and growing e-commerce industries. As the delivery services of public logistics organizations have a lasting impact on customer behavior, logistics organizations are using innovative, customer-centric, and cost-effective strategies to offer customers convenient, attractive, and effective service solutions. The current study has been undertaken to analyze the effectiveness of each element of quality services of delivery services. Qualitative and quantitative research approaches were implemented based on a hundred respondents in identifying the critical issues based on the SERVQUAL method, heterogeneous customer satisfaction index (HCSI), and mapping out prioritizing the most critical problem. The study results reveal that customers are susceptible to the responsive, assurance, and empathy dimensions. These three of five dimensions are adversely influencing the satisfaction of customers.